Friday
March 24, 2017

Post a New Question

Posted by on Wednesday, April 18, 2012 at 8:52pm.

x= √3x+12+2

  • Algebra 2 - , Wednesday, April 18, 2012 at 9:49pm

    You will need brackets to show where the square root ends
    the way you have it ...
    x - √3x = 14
    x(1-√3) = 14
    x = 14/(1-√3)

    something tells me that is not what you meant

    e.g.
    is it x = √(3x+12) + 2 ?

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question